Visceral Leishmaniasis (Kala-azar) in Merti Sub-County, Isiolo County: A Case of Socio-Cultural Challenges - Mwiti Marangu, Victor; Robert Mburugu Kei, Prof. Robert Mburugu Kei; Dorothy Kagendo Kithinji, Dr. Dorothy Kagendo (African Journal of Science, Technology and Social Sciences, 2024)
Introduction: Visceral Leishmaniasis (VL) also known as Kala-azar is a fatal neglected tropical disease (NTD) with a 95% fatality rate among untreated cases. Although there is little information available about the disease’s prevalence in Isiolo County, it is extremely endemic in a number of villages in Merti Sub-County. Case Presentation: In this case presentation, a family of three children resulted to traditional therapy when the children contracted Kala-azar. All the three children exhibited signs of fever, loss of appetite, swollen abdomen, vomiting, and general weakness. Discussion: Low levels of Visceral Leishmaniasis knowledge, ignorance characterized by cultural beliefs, and the use of local therapies are among socio-cultural challenges impeding implementation of effective Kala-azar control strategies in Isiolo County. Conclusion: This case highlights the importance of focused community awareness for prompt and efficient diagnosis and treatment to lower Kala-azar prevalence, monitoring the burden and spread of the disease as well as lowering transmission.